(3UjO GdNGWQs - (3GHf GdLhRj, YHO GdQMef Hf Ydj Hf eMeO,s 508-597 (3g`(B.s; (3gfOGhj, YHO GdMejO CMeO jhSa,s 1962- ((3HjQhJ (B:s (3GdecJHI GdYUQjI,s, 2005)
(3jJfGhd GdcJGH eSGFd OjfjI cKjQI(B.s
Keywords: (3GdhYX hGdEQTGOs; (3GdOYhI GdESdGejIs